Kritik Sosial dalam Anime "Death Note": Social Criticism in The Anime Death Note - Simbolon, Billy; Arfianty, Rani Arfianty (Jurnal Pendidikan Bahasa Jepang Undiksha, 2025)
This article focuses on the Death Note anime by Tsugumi Ohba and Takeshi Obata. Aired in Japan from October 3 2006 to June 26 2007, it tells the story of a high school student named Light Yagami who finds a Death Note belonging to a Shinigami (God of Death) named Ryuk. This research uses a qualitative method, which analyzes based on themes, dialogue and the actions of the main characters. The aim of this research is to analyze the influence and impact of social criticism in Death Note such as abuse of power, authoritarianism and moral relativism. The results of the data analysis show that the anime Death Note provides profound social criticism through the exploration of themes such as abuse of power, ethical ambiguity, the role of the media, and the limitations of the human justice system. This work is a reminder that power must always be balanced with responsibility, and justice must be achieved through wisdom, not tyranny.